Parental Acceptance of Behavior Management Techniques in Pediatric Dental Patients and Associated Factors: A Cross-Sectional Study - Tran P.T. (2023)
Parent’s perception of behavior management techniques (BMTs) plays a decisive role in BMTs use for children. This study aimed to investigate the acceptance of commonly used BMTs by parents of preschoolers in Vietnam. All parents in 4 kindergartens in Hanoi were approached onsite, then data were collected through a web-based survey. Parents were asked to watch and rate their acceptance of 10 BMTs video clips using visual analogue scale (VAS). Mean VASs for BMT acceptance were analyzed using Wilcoxon Signed Ranks Test. Association between mean VAS and factors were tested using one-way ANOVA and independent t-test. The level of confidence was set at 95%. There were 107 parents completed the survey. Most were mothers holding bachelor’s degrees. The most accepted BMTs were positive reinforcement and distraction, followed by (2) Tell-Show-Do, voice control, (3) parent presence/absence, (4) active restraint, and (5) general anesthesia, passive restraint, oral sedation, nitrous oxide/oxygen. Acceptance of restraint and pharmacological techniques was higher in parents whose children attended public kindergarten. Tell-Show-Do was accepted significantly higher by parents of relatively older children. Oral sedation was accepted significantly higher by parents of girls. Communicative techniques were much more accepted than pharmacological techniques and restraint by device among Vietnamese parents.